Understanding the risk and protective factors associated with obesity amongst Libyan adults - a qualitative study - H. Lemamsha; C. Papadopoulos; G. Randhawa (BMC, 2018)
Abstract Background There are a range of multifaceted behavioural and societal factors that combine to contribute to the causes of obesity. However, it is not yet known how particularly countries' cultural norms are contributing to the global obesity epidemic. Despite obesity reaching epidemic proportions in Libya, since the discovery of oil in 1959, there is a lack of information about obesity in Libyan adults. This study sought to explore the views of key informants about the risk and protective factors associated with obesity among Libyan men and women. Methods A series of qualitative semi-structured interviews were conducted with Libyan healthcare professionals and community leaders. Results Eleven main themes (risk and protective factors) were identified, specifically: socio-demographic and biological factors, socioeconomic status, unhealthy eating behaviours, knowledge about obesity, social-cultural influences, Libya's healthcare facilities, physical activity and the effect of the neighbourhood environment, sedentary behaviour, Libyan food-subsidy policy, and suggestions for preventing and controlling obesity. Conclusions Key recommendations are that an electronic health information system needs to be implemented and awareness about obesity and its causes and consequences needs to be raised among the public in order to dispel the many myths and misconceptions held by Libyans about obesity. The current political instability within Libya is contributing to a less-active lifestyle for the population due to security concerns and the impact of curfews. Our findings have implications for Libyan health policy and highlight the urgent need for action towards mitigating against the obesity epidemic in Libya.